LABOR COMMUNICATIONS WITHIN THE IMPLEMENTATION OF LEAN TECHNOLOGIES AT SMALL ENTERPRISES - Kuizheva, Saida; Zarubin, Vladimir; Zadorozhnaya, Luydmila; Khachemizov, Anzor; Ahmar, Ayham (Revista Inclusiones, 2019)
The purpose of this article is to study the characteristics distinguishing small and medium enterprises from large ones in the context of the implementation of the lean production principle. Models and tools of lean production are highly demanded for the performance of a task of labor ramp-up at enterprises and organizations. The methodological basis of the study is a systemic approach to the process of implementation of lean production theory at industrial enterprises.